Multiple infections with Omicron variants increase breadth and potency of Omicron-specific neutralizing antibodies - Lei You; Luning Zhang; Shengqun Ouyang; Bo Gao; Yanan Li; Jialu Li; Ningbo Wu; Hong Wang; Shiqi Sun; Jinfeng Li; Zi Yin; Ziyang Xu; et al. (Cell Discovery)
Abstract Despite high vaccination rates, highly evolved Omicron variants have caused widespread infections and, in some cases, recurrent infections in the human population. As the population continues to be threatened by new variants, it is critical to understand how the dynamic cross-reactive antibody response evolves and affects protection. Here, we longitudinally profiled neutralizing antibodies in individuals who experienced three Omicron waves in China over an 18-month period following the lifting of the COVID restriction. We found that individuals with BA.5/BF.7 and XBB dual infections had increased breadth and neutralizing potency of Omicron-specific antibodies compared to those with a BA.5/BF.7 single infection, and were thus more resistant to JN.1/XDV.1 infection in the third wave. During the second infection, a new imprint based on the previously infected variant was established, and the antibodies developed high cross-reactivity against the Omicron variants and less against vaccine-derived WT SARS-CoV-2. Our results suggest that the high titer and breadth of cross-reactive antibodies from multiple infections may be protective against future infection with Omicron variants such as JN.1, but may still be vulnerable to antigenically advanced subvariants such as KP.3.1.1 and XEC.